Piloted flight simulation for helicopter operation to the Queen Elizabeth class aircraft carriers - Kelly, M.F.; White, M.D.; Hodge, S.J. (My University, 2017)
Flight simulation is being used to inform the First of Class Flight Trials for the UK’s new Queen Elizabeth Class (QEC) aircraft carriers. The carriers will operate with the Lockheed Martin F-35B Lightning II fighter aircraft, i.e. the Advanced Short Take-Off and Vertical Landing variant of the F-35. The rotary wing assets that are expected to operate with QEC include Merlin, Wildcat, Chinook and Apache helicopters. An F-35B flight simulator has been developed and is operated by BAE Systems at Warton Aerodrome. The University of Liverpool is supporting this project by using Computational Fluid Dynamics (CFD) to provide the unsteady air flow field that is required in a realistic flight simulation environment. This paper is concerned with a research project that is being conducted using the University’s research simulator, HELIFLIGHT-R, to create a simulation environment for helicopter operations to the QEC. The paper briefly describes how CFD has been used to model the unsteady airflow over the 280m long aircraft carrier and how this is used to create a realistic flight simulation environment. Results are presented from an initial simulation trial in which test pilots have used the HELIFLIGHT-R simulator to conduct simulated helicopter landings to two landing spots on the carrier, one in a disturbed air flow and the other in clean air. As expected, the landing to the spot in disturbed air flow requires a greater pilot workload, shows greater deviation in its positional accuracy and requires more control activity. This initial trial is the first of a planned series of simulated helicopter deck landings for different wind angles and magnitudes.